2019
DOI: 10.1080/09513590.2019.1576620
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of two combinations of myo-inositol and D -chiro-inositol in women with polycystic ovary syndrome undergoing ICSI: a randomized controlled trial

Abstract: The purpose of this study was to evaluate the effect of two doses of D-chiro-inositol (DCI) in combination with Myo-inositol (MYO) in women with PCOS undergoing ICSI. This was a multicenter controlled, randomized, double-blind parallel group study with two MYO-DCI formulations for 12 weeks. The study group (SG) was administered 550 mg of MYO þ 150 mg of DCI twice daily; the control group (CG) was administered 550 mg of MYO þ 13.8 mg of DCI twice daily. The participants comprised 60 women with PCOS undergoing I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 29 publications
1
14
0
6
Order By: Relevance
“…Although other ratios were analyzed, these combinations were without a scientific rationale [ 51 ]; conversely the 40:1 ratio that may appear arbitrary, actually is similar to the plasma ratio reported in healthy women [ 51 , 52 , 53 , 54 ], thus supporting its supplementation to restore the physiological concentrations of myo-Ins and D-chiro-Ins. On the other hand, one study [ 55 ] considers the amount of DCI in the 40:1 ratio very low and proposes combining the two inositols using D-chiro-Ins at high doses. However, some concerns arise when D-chiro-Ins is used at high doses and for prolonged time, as demonstrated in a recent paper by Bevilacqua et al [ 56 ] and discussed below.…”
Section: Evidence-based Effects Of Inositols Supplementation On Human Reproductionmentioning
confidence: 99%
“…Although other ratios were analyzed, these combinations were without a scientific rationale [ 51 ]; conversely the 40:1 ratio that may appear arbitrary, actually is similar to the plasma ratio reported in healthy women [ 51 , 52 , 53 , 54 ], thus supporting its supplementation to restore the physiological concentrations of myo-Ins and D-chiro-Ins. On the other hand, one study [ 55 ] considers the amount of DCI in the 40:1 ratio very low and proposes combining the two inositols using D-chiro-Ins at high doses. However, some concerns arise when D-chiro-Ins is used at high doses and for prolonged time, as demonstrated in a recent paper by Bevilacqua et al [ 56 ] and discussed below.…”
Section: Evidence-based Effects Of Inositols Supplementation On Human Reproductionmentioning
confidence: 99%
“…On the contrary, three meta-analyses failed to conclude on the effect of MI in women with PCOS [14,21,22]. Mendoza [14] reported, in 8 studies involving 1019 PCOS women, a not significant trend towards improvement in egg quality (OR: 2.2; 95% CI 0.8-5.8), embryo quality (OR 1.6; 95% CI 0.3-6.7) and pregnancy rate (OR: 1.2; 95% CI 0.8-1.8) with MI administration.…”
Section: Impact Of MI In Ivf/icsimentioning
confidence: 99%
“…He concluded that future studies of dose, size and duration of DCI are necessary. Since, two other controlled, randomized, double blind parallel group studies of the same author [21,22] showed (after 12 weeks of treatment in women with PCOS undergoing ICSI), (i) a significant increase of pregnancy and live birth rates (65.5 vs. 25.9; p: 0.003, and 55.2 vs. 14.8; p: 0.002, respectively) and a decrease of ovarian hyperstimulation syndrome (3.4 vs. 18.5%; p: 0.07) with a 3.6:1 MI/DCI ratio compared to a 40:1 ratio [21]; (ii) a positive influence (p: 0.006) on the quality of the cytoplasm of the oocyte with a 1.8:1 ratio compared to a 20:1 ratio [22]. So, the debate on the appropriate MI/DCI ratio remains unresolved.…”
Section: Impact Of MI In Ivf/icsimentioning
confidence: 99%
“…Following title and abstract screening, 408 full-text articles were retrieved and screened for eligibility. Of them, 307 articles were excluded, and 101 RCTs [20-32, 33, 34-43, 44, 45- [121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136], however, they could not be added to our analysis due to the following causes: five studies failed to meet our BMI criteria , three studies included irrelevant interventions [133][134][135], two studies had an open-label design [127,128], two studies measured different outcomes [131,132], one study had a cost-effectiveness design [121], one study had a post-hoc design [129], one study had no treatment control [122], and one study included pregnant patients [130]. Additionally, the bibliography of the included RCTs was manually searched, but no further records were added.…”
Section: Characteristics and Quality Of Included Studiesmentioning
confidence: 99%